Surgical Infrarenal "Neo-neck" Technique During Elective Conversion after EVAR with Suprarenal Fixation. Issue 2 (August 2015) - Bonvini, S.; Wassermann, V.; Menegolo, M.; Scrivere, P.; Grego, F.; Piazza, M.
Abstract : Objectives: Conversion of a previous endovascular aneurysm repair (EVAR) with suprarenal fixation is a challenging situation even in the elective setting. The outcomes of a technique based on preservation of the first proximal covered stent of the endograft, used as a "neo-neck" for proximal anastomosis, are presented. Methods: From 2001 to 2014, nine patients underwent elective conversion of a previous suprarenally fixed EVAR. After supraceliac clamping, the aneurysm sac was opened and the endograft identified; the fabric was cut beyond the first covered stent together with its native aortic wall in order to create a "neo-neck." An aortic balloon was inflated into the visceral aorta to avoid back bleeding. A Dacron bifurcated tube graft (Intergard, Maquet) was then sutured to the neo-neck mimicking endobanding, passing the stitches into the aortic wall and the first covered stent. Results: The mean age was 68 years (range, 52–84 years). The stent grafts removed were four Zenith (Cook Medical), three Endurant (Medtronic), and two E-vita (Jotec). The indication for conversion was type 1A ( n = 2), type 2 ( n = 2), and type 3 ( n = 1) endoleak, complete endograft thrombosis ( n = 2), and abdominal pain with sac enlargement with no radiological sign of endoleak ( n = 2). Blood loss was 1, 428 mL (range 500–3, 000 mL); the visceral ischemic time to perform the proximal anastomosis was 23.5 min ± 2.3 min). The post-operative complication rate was 11% ( n = 1/9) related to a case of sac wall bleeding requiring re-intervention; mortality at 30 days was 0%. At 22 months (range, 8–41) the computed tomography angiogram demonstrated no signs of leaks or anastomotic pseudoaneurysm. Conclusion: Preservation of the proximal covered stent of an endograft with suprarenal fixation used as an infrarenal "neo-neck" with incorporation of the aorta to the suture line during elective surgical explantation simplifies the procedure, and can be achieved with very low early morbidity and mortality; furthermore, it seems to be durable over mid-term follow up.